Quality of Work-Life Among Employees of The University of The Gambia - Saidykhan, Lamin W.; Ceesay, Lamin B. (Archives of Business Research, 2020)
Quality of work-life (QWL) is concerned with the welfare and satisfaction of employees on the job as well as off the job. The purpose of this research is to undertake a combination of descriptive study - to ascertain and explain the level of QWL among the employees of the University of The Gambia – and hypothesis testing - to establish the relationship between QWL and demographic factors of the respondents. Summary of the results indicate that interestingly, four aspects of QWL stand in employees’ evaluation as “moderate-to-high” motivators such as relations and co-operations, autonomy of work, and organizational culture and climate. However, to “moderate-to-low” level of motivation with QWL aspects has been reported, such as job satisfaction and job security, training and development, work environment, adequacy of resources, compensation and rewards, and facilities. Moreover, results also indicate that respondents differ significantly in their QWL in terms of designation, education and monthly salary. They however do not differ significantly in their QWL in terms of gender, age and work experience. Our original contribution to research is that we examine an application of QWL in a context (i.e. UTG) that has not existed in extant literature. The result also provides managerial implications that is unique to the case under study, which confirms the multidisciplinary nature of QWL. Thus, although these results slightly vary with few studies, our results confirm findings of several other scholars.